Peer Tutoring Interventions for Students With or At-Risk for Emotional and Behavioral Disorders: A Systematic Review of Reviews. Issue 3 (May 2023) - Bowman-Perrott, Lisa; Ragan, Kelsey; Boon, Richard T.; Burke, Mack D.
This systematic review of reviews is the first to summarize peer tutoring outcomes for students with or at-risk for emotional and behavioral disorders (EBD). Eleven narrative literature reviews, three systematic reviews, and two meta-analyses of peer tutoring interventions that met inclusion criteria were summarized. Participants across the 16 reviews included more than 2, 404 students with or at-risk for EBD in pre-kindergarten through grade 12 across 73 individual, unduplicated studies. Findings support the efficacy of peer tutoring for students with or at-risk for EBD regarding academic and behavioral outcomes. Lessons learned, and implications for research and practice derived from these reviews are provided.